Posology and Serum-/Xeno-Free Engineered Adipose Stromal Cells Cell Sheets - Ochiai, Jun; Villanueva, Larakaye; Niihara, Hope; Niihara, Yutaka; Oliva, Joan (Frontiers in Cell and Developmental Biology, 2022)
Well-characterized adipose stem cells and chemically defined culture media are important factors that control the production of the cell sheet, used in translational medicine. In this study, we have developed and engineered multilayer adipose stem cell cell sheets (ASCCSs) using chemically defined/serum-free culture media: undifferentiated or differentiated into osteoblasts and chondrocytes. In addition, using the cell sheet transmittance, we estimated the number of cells per cell sheet. Undifferentiated ASCCSs were engineered in 10 days, using serum-free/xeno-free culture media. They were CD29+, CD73+, CD90+, CD105+, HLA-A+, and HLA-DR-. ASCCSs differentiated into chondrocytes and osteoblasts were also engineered using chemically defined and animal-free culture media, in only 14 days. The addition of an ROCK inhibitor improved the chondrocyte cell sheet engineering. The decrease in the cell sheet transmittance rate was higher for the osteoblast cell sheets due to the intracellular Ca2+ accumulation. The estimation of cell number per cell sheet was carried out with the transmittance, which will provide important information for cell sheet posology. In conclusion, three types of ASCCSs were engineered using serum-free, xeno-free culture media, expressing their specific markers. Their transmittance measurement allowed estimating the number of cells per cell sheet, with a non-invasive methodology.